Combining ability for resistance to Fusarium wilt and yield in black bean - Torres, Mário Henrique Rodrigues Mendes; Souza, Thiago Lívio Pessoa Oliveira de; Melo, Leonardo Cunha; Pereira, Helton Santos (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to investigate the genetic control of black bean (Phaseolus vulgaris) and to select parents and segregating populations with high resistance to Fusarium wilt, high yield, and greater 100-seed weight (100SW), using a partial diallel cross. Twenty-five populations were obtained from two groups of parents – the first with five parents resistant to and the second with five parents susceptible to Fusarium wilt. The segregating populations were evaluated in experiments in three years/generations for reaction to Fusarium wilt, yield, and 100SW in an area naturally infested with the pathogen. The diallel analysis showed additive and nonadditive effects in control of the three studied traits, with predominance of additive effects. CNFP 15194, CNFP 15207, and 'BRS Esplendor' are the genotypes with high and negative general combining ability estimates (ĝi = -0.59, -0.76, and -0.13, respectively), being recommended for use as parents for resistance to Fusarium wilt. Among them, CNFP 15194 also forms populations with a greater 100SW (ĝi = 0.69). The BRS FP403 cultivar is recommended as a parent to increase yield (ĝi = 218) and 100SW (ĝi = 1.46). Six populations were selected to obtain black bean lines that combine resistance to Fusarium wilt, high yield, and high 100SW.